The concept of Triple Bottom Line Planetary Dimensions in Learning at Beauty Courses and Training Institutions - Permatasari, Selgi Okta; Redjeki, Endang Sri; Choiro, Umu Da’watul (Universitas Negeri Malang, 2024)
Beauty courses and training institutions are one of the non-formal educational institutions that provide lifelong education for the development of a person's skills in the field of beauty. The institute provides output of graduates who are competent in the beauty industry. Learning that is carried out by the institution usually produces plastic waste and contains chemicals. This encourages the institution to apply the planetary dimension of the triple bottom line to sustain the institution in the future. The purpose of this research is to find out the application of the concept of the planet dimension of the triple bottom line in learning at courses and beauty institutions. This research uses a qualitative case study method with data sources coming from observation, interviews and documentation studies. The data analysis used is mills and huberman's and data validation uses triangulation of time, sources and techniques. This study found that the concept of the triple bottom line planet is applied through the components of the learning system in the form of methods and strategies. Keywords: Concept of planet, beauty courses and training institutions, learning systems.